Caracterização de um sistema piezelétrico para geração de energia elétrica - Kuhn, Gustavo Gomes (2014)
This dissertation presents a study on low power electricity generation using piezoelectric materials, in particular patches of PZT-4 model. The system adopted is of the type cantilever beam with a mass on the free end of the beam. It has piezoelectric patches glued to the beam and is subjected to external forces harmonics in the excitation frequency bands in the order of 0~35 Hz. The energy generator uses the concept of energy harvesting, which withdraws from the external environment, energy that would otherwise be lost. The overall objective is to characterize the piezoelectric system for generating electricity from low power. A cam follower (shaker) was used to generate mechanical motion (external force). Above, is an accomplished mathematical modeling of the PZT patches employing the concept of Equivalent Circuit Model – ECM. Some topologies conditioners circuits of AC-DC signal are also presented, where the model was employed Hybrid Synchronized Switch Harvesting on Inductor. Two excitation frequencies were investigated 2.5 Hz and 19.5 Hz. The results presented and discussed through graphs: of frequency response of acceleration, acceleration of the system, frequency response of admittance, generated voltage, electric current, charging time of capacitors and electrical power generated in the output of the circuit. The contribution of this research was to present the characterization of the electromechanical behavior of a piezoelectric system to generate electricity for the two studied excitation frequencies. The research presents the involution the relationships of some parameters, such as frequency response of excitement, with ratio equal to 87.5 and electric power generated ratio equal to 1.07.